Prefoldin Function in Cellular Protein Homeostasis and Human Diseases - Tahmaz, Ismail; Shahmoradi Ghahe, Somayeh; Topf, Ulrike (Frontiers in Cell and Developmental Biology, 2022)
Cellular functions are largely performed by proteins. Defects in the production, folding, or removal of proteins from the cell lead to perturbations in cellular functions that can result in pathological conditions for the organism. In cells, molecular chaperones are part of a network of surveillance mechanisms that maintains a functional proteome. Chaperones are involved in the folding of newly synthesized polypeptides and assist in refolding misfolded proteins and guiding proteins for degradation. The present review focuses on the molecular co-chaperone prefoldin. Its canonical function in eukaryotes involves the transfer of newly synthesized polypeptides of cytoskeletal proteins to the tailless complex polypeptide 1 ring complex (TRiC/CCT) chaperonin which assists folding of the polypeptide chain in an energy-dependent manner. The canonical function of prefoldin is well established, but recent research suggests its broader function in the maintenance of protein homeostasis under physiological and pathological conditions. Interestingly, non-canonical functions were identified for the prefoldin complex and also for its individual subunits. We discuss the latest findings on the prefoldin complex and its subunits in the regulation of transcription and proteasome-dependent protein degradation and its role in neurological diseases, cancer, viral infections and rare anomalies.